2000
DOI: 10.1046/j.1365-3040.2000.00527.x
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of glycinebetaine in rice plants: evaluation using transgenic rice plants with a gene for peroxisomal betaine aldehyde dehydrogenase from barley

Abstract: Glycinebetaine is synthesized in plants by the two-step oxidation of choline, with betaine aldehyde as the intermediate. The reactions are catalyzed by choline monooxygenase and betaine aldehyde dehydrogenase. Rice plants, which do not accumulate glycinebetaine, possess a gene encoding betaine aldehyde dehydrogenase, whose activity is detectable at low levels. To evaluate the compatibility in rice of glycinebetaine on growth and tolerance to salt, cold and heat, we produced transgenic rice plants by introducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(55 citation statements)
references
References 32 publications
1
52
1
1
Order By: Relevance
“…Indeed, recent papers by Blumwald's group (5,18,19) elegantly showed that overexpression of a single vacuolar Na ϩ ͞H ϩ antiporter gene in plants such as oil seed crop Brassica napus permitted them to grow, flower, and produce seeds in the presence of 0.2 M NaCl. Hitherto, we have examined the properties of various transgenic plants by using the dnaK gene from A. halophytica (25,26), the GS2 gene from rice (8), bet genes from several species (27,28), Mn-SOD gene from yeast (29), and the katE gene from E. coli. From careful comparison of these transformants under the same conditions and more systematic approaches, the molecular breeding of salt-tolerant plants applicable in the fields should be possible.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent papers by Blumwald's group (5,18,19) elegantly showed that overexpression of a single vacuolar Na ϩ ͞H ϩ antiporter gene in plants such as oil seed crop Brassica napus permitted them to grow, flower, and produce seeds in the presence of 0.2 M NaCl. Hitherto, we have examined the properties of various transgenic plants by using the dnaK gene from A. halophytica (25,26), the GS2 gene from rice (8), bet genes from several species (27,28), Mn-SOD gene from yeast (29), and the katE gene from E. coli. From careful comparison of these transformants under the same conditions and more systematic approaches, the molecular breeding of salt-tolerant plants applicable in the fields should be possible.…”
Section: Discussionmentioning
confidence: 99%
“…22 However, transgenic rice plants expressing functional BADH gene from barley could convert exogenously applied betaine aldehyde to GB at a level better than WT plants. 23 Introduction of spinach CMO gene in rice also resulted in accumulation of detectable amount of GB. 21 Therefore, rice produces highly reduced amount of functional BADH and CMO proteins resulting in undetectable amount of GB synthesis.…”
Section: Glycinebetaine: Roles Mechanism and Emerging Conceptsmentioning
confidence: 99%
“…Other pathways of betaine synthesis have also been reported in animals and microorganisms (Sakamoto and Murata 2002). Genes encoding enzymes involved in betaine synthesis has been used to produce transgenic plants that show improved tolerance to salinity and other environmental stresses (Holmström et al 2000, Jia et al 2002, Kishitani et al 2000, Li et al 2003, Quan et al 2004.…”
Section: Introductionmentioning
confidence: 99%